Can a theoretical framework help to embed alcohol screening and brief interventions in an endoscopy day-unit?. Issue 1 (24th March 2015) - O'Neill, G; Masson, S; Bewick, L; Doyle, J; McGovern, R; Stoker, E; Wright, H; Newbury-Birch, D
Abstract : Introduction and aims: The National Institute for Health Care and Excellence recommend that alcohol screening and brief intervention (ASBI) should be routinely implemented in secondary care. This study used theoretical frameworks to understand how health professionals can be supported to adapt their behaviour and clinical practice. Design and methods: Staff training and support was conducted using theoretical frameworks. A 12-week study, delivering ASBI was carried out as part of routine practice in an endoscopy day-unit. Anonymised patient data were collected using the Alcohol Use Disorders Identification Tool (AUDIT) and whether patients received a brief intervention. Staff completed the Shortened Alcohol and Alcohol Problems Perceptions Questionnaire at three time points and took part in a focus group both pre and post study. Results: For staff, levels or role adequacy, role legitimacy, motivation to discuss alcohol, security in their role, job satisfaction and commitment to working with patients who drink increased during the time of the study. 1598 individual patients were seen in the department in the timeframe. Of these, 1180 patients were approached (74%); 18% (n=207) of patients were AUDIT positive. Discussion: This study has shown that it is possible to reach a high number of patients in a busy hospital out-patient department and deliver ASBI by working with staff using theoretical frameworks for training. Embedding evidence-based public health interventions into routine clinical environments is complex. The social system in which professionals operate requires consideration alongside individual professionals' real and perceived barriers and facilitators to change.